Phase change material integrated bow-tie resonator for programmable terahertz metasurface for enabling 6G communications - Nawani Vinay Dhaneshkumar (Nanyang Technological University, 2022)
Terahertz (THz) waves (0.1 – 10 THz) in the electromagnetic spectrum have a high potential to realize several futuristic applications such as THz imaging, 6G wireless communication, security, haptics communication and many more. These ultra-high frequency waves promise to boost the performance of many conventional technologies. Due to its high potential, it becomes very important to develop devices that could efficiently manipulate THz waves. One of the biggest challenges is that naturally occurring materials have very limited response to THz waves and hence the development of THz devices has remained relatively slow. This paves the way for creation of artificial structures having specialised optical properties to manipulate the THz waves. Such structures are known as metasurfaces. Artificially manufactured materials termed has “metamaterials” have shown great promise in the efficient interaction and manipulation of THz waves. A metamaterial consists of sub-wavelength patterned structures in an array type arrangement whose properties are primarily determined by the pattern shape and size. Hence, metamaterials are functionally versatile, extremely thin and light weight and spectrally scalable. Furthermore, active materials responsive to external stimulus can be incorporated within the unit cell geometry to enable tunable THz response which are then termed as “dynamic metamaterials”. The ultimate form of dynamic metamaterials is the one where each of the unit cell can be controlled independently and are termed as “programmable metamaterials”. A single programmable THz metamaterial can be dynamically reconfigured to function either as a spatial light modulator, beam steerer, beam splitter, or polarization convertor with several other promising applications. In this thesis, we investigate the use of germanium antimony telluride (GST) phase change material as the active material to realize programmable THz metamaterials. GST possesses strikingly contrasting material properties across its various crystallographic phases that can be exploited for multilevel reconfiguration of THz wave. The phase change in GST is a thermally driven process and hence to enable an integrated solution, microheaters need to be used. We conceptualize, design, and fabricate a novel bow-tie shaped resonator which serves as a unit cell for the programmable THz metamaterial and acts as a microheater to enable efficient reconfiguration of GST via electrical stimulus route. The as-deposited GST is amorphous and has low electrical conductivity and upon heating it to its phase change temperature of 150 °C, the phase of GST becomes highly crystalline that is electrically conductive. This specific material property of GST is used to achieve multilevel modulation of THz waves using the bow-tie THz metamaterial. It is important to note that the phase change in GST is non-volatile and the electrical control will enable spatial localization reconfiguration in the future, which will be critical for the realization of programmable THz metamaterials. The proposed GST integrated programmable THz metamaterials will facilitate the development of THz reconfigurable intelligent surfaces, spatial light modulators for compressive THz imaging, polarization convertors in chemical and biological material characterization.